Defining factors for choosing medical specialty in Brazil - Cruz, José Arnaldo Shiomi da; Sandy, Natascha Silva; Vannucchi, Tiago Ribeiro; Gouveia, Éder Maxwell; Passerotti, Carlo Camargo; Bruschini, Homero; Srougi, Miguel (Revista de Medicina, 2010)
Background. Choosing medical specialty is complex and depends on multiple factors. The importance of the different factors varies across the world, according to different values and systems of education. The purpose of this study is to identify the determining factors involved in this choice among medical students in Brazil. Methods. A questionnaire was sent by email to medical students from first to sixth year of a selected institution, asking demographic information and the evaluation of factors that may influence the choice of the medical specialty. Results. The mean age was 22 years. Regarding the influence of relatives, 42.5% of the students has at least one physician as a close relative, the most common specialties of this relative were: Pediatrics, Gynecology and Obstetrics and Ophthalmology. 19% of the respondents declared being sure of the career when they entered University, while 22.2% of them were sure about the choice at the occasion of the study. Affinity for the specialty and lifestyle were evaluated as important or very important by more than 95% of respondents. Urge to earn money fast, short time of medical residency, high initial profit and family influence were the factors evaluated as less important by the respondents. Almost half of the respondents (49.7%) rejected a specialty they had strongly cogitated once. The main reasons for this were the lifestyle and the fact that they discovered not having affinity for the specialty. Conclusions. Affinity and medical lifestyle are the defining factors in choosing and rejecting a medical specialty in Brazil.